Transcriptome profiling of genes regulated by phosphate-solubilizing bacteria Bacillus megaterium P68 in potato (Solanum tuberosum L.) - Lin, Lizhen; Li, Chengchen; Ren, Zongling; Qin, Yuzhi; Wang, Ruilong; Wang, Jia; Cai, Jianying; Zhao, Lanfeng; Li, Xiaobo; Cai, Yanfei; Xiong, Xingyao (Frontiers in Microbiology, 2023)
The insoluble phosphorus in the soil is extremely difficult to be absorbed and used directly through the potato root system. Although many studies have reported that phosphorus-solubilizing bacteria (PSB) can promote plant growth and uptake of phosphorus, the molecular mechanism of phosphorus uptake and growth by PSB has not been investigated yet. In the present study, PSB were isolated from rhizosphere soil in soybean. The data of potato yield and quality revealed that the strain P68 was the most effective In the present study, PSB identification, potato field experiment, pot experiment and transcriptome profiling to explored the role of PSB on potato growth and related molecular mechanisms. The results showed that the P68 strain (P68) was identified as Bacillus megaterium by sequencing, with a P-solubilizing ability of 461.86 mg·L−1 after 7-day incubation in National Botanical Research Institute’s Phosphate (NBRIP) medium. Compared with the control group (CK), P68 significantly increased the yield of potato commercial tubers by 17.02% and P accumulation by 27.31% in the field. Similarly, pot trials showed that the application of P68 significantly increased the biomass, total phosphorus content of the potato plants, and available phosphorus of the soil up by 32.33, 37.50, and 29.15%, respectively. Furthermore, the transcriptome profiling results of the pot potato roots revealed that the total number of bases was about 6G, and Q30 (%) was 92.35–94.8%. Compared with the CK, there were a total of 784 differential genes (DEGs) regulated when treated with P68, which 439 genes were upregulated and 345 genes were downregulated. Interestingly, most of the DEGs were mainly related to cellular carbohydrate metabolic process, photosynthesis, and cellular carbohydrate biosynthesis process. According to the KEGG pathway analysis, a total of 46 categorical metabolic pathways in the Kyoto Encyclopedia of Genes and Genomes (KEGG) database were annotated to 101 DEGs found in potato roots. Compared with the CK, most of the DEGs were mainly enriched in glyoxylate and dicarboxylate metabolism (sot00630), nitrogen metabolism (sot00910), tryptophan metabolism (sot00380), and plant hormone signal transduction (sot04075), and these DEGs might be involved in the interactions between Bacillus megaterium P68 and potato growth. The qRT-PCR analysis of differentially expressed genes showed that inoculated treatments P68 significantly upregulated expression of the phosphate transport, nitrate transport, glutamine synthesis, and abscisic acid regulatory pathways, respectively, and the data from qRT-PCR were consistent with that obtained from RNA-seq. In summary, PSB may be involved in the regulation of nitrogen and phosphorus nutrition, glutaminase synthesis, and abscisic acid-related metabolic pathways. This research would provide a new perspective for studying the molecular mechanism of potato growth promotion by PSB in the level of gene expression and related metabolic pathways in potato roots under the application of Bacillus megaterium P68.